Applied engineering failure analysis : theory and practice /: theory and practice. (2015) - Qua, Hock-Chye; Tan, Ching-Seong; Wong, Kok-Cheong; Ho, Jee-Hou; Wang, Xin; Yap, Eng Hwa; Ooi, Jong-Boon; Wong, Yee-Shiuan
No abstract available